A STUDY OF 8(th) GRADERS' PERCEPTIONS OF SOCIO-CULTURAL PERSPECTIVE OF CREATIVITY BY USING INFORMATION TECHNOLOGY TOOLS IN REALISATION OF HOMEWORK GOALS - (:unkn) unknown (TURKISH ONLINE JOURNAL EDUCATIONAL TECH-TOJET, 2011)
The study aims at evaluating the perceptions of 8(th) graders towards the use of information technologies ranging from the internet and multimedia tools in socio-cultural perspective of creativity while they are doing their homework in the light of the National Education Ministry's regulation related to elementary and secondary school students' extra-curricular activities. The population of the research that was realised by data collected through survey method consists of 8(th) grade students in elementary and secondary schools in Istanbul. Randomly chosen 435 students from five schools in Istanbul make the sample of the research. In terms of students' perceptions, results of the study show that regardless of gender, students enjoy discovering and exploiting online and offline resources through problem solving skills especially when they have the opportunity to do this on their own, which also shows that they think they feel more confident, mobile and creative in cyber but socio-cultural reality.
Keywords: homework; creativity; information technologies; multimedia